Penggunaan Media Film Animasi Untuk Meningkatkan Pemahaman Konsep Gaya Pada Siswa Kelas IV SDI Watujara - Maria Fransiska Karhe (Program Studi Pendidikan Ekonomi, Universitas Flores, 2020)
This research was conducted based on the discovery of problems in the science learning process experienced by students, namely the low understanding of the concept of style in grade IV SDI Watujara students. The purpose of this study was to determine the increase in understanding the concept of science by applying animated film media. The research was carried out in the Classroom Action Research (PTK) stage design by Kemmis and Mc Taggart which included the planning stages (Plan), the implementation stage (Act), the observation stage (observe) and the reflection stage (reflect). The data taken is data on students' conceptual understanding. Data collection was carried out by using observation techniques, field notes, tests and interviews. Data were analyzed using qualitative descriptive techniques. The results of the research that had been carried out in two cycles showed an increase in students' conceptual understanding after the application of animated film media.